Bash Quick Start Guide Get up and running with shell scripting with Bash - Ryder, Tom (Packt Publishing Limited, 2018)
bLearn how to write shell script effectively with Bash, to quickly and easily write powerful scripts to manage processes, automate tasks, and to redirect and filter program input and output in useful and novel ways. /b h4Key Features/h4 ulliDemystify the Bash command line /li liWrite shell scripts safely and effectively /li liSpeed up and automate your daily work/li/ul h4Book Description/h4 Bash and shell script programming is central to using Linux, but it has many peculiar properties that are hard to understand and unfamiliar to many programmers, with a lot of misleading and even risky information online. Bash Quick Start Guide tackles these problems head on, and shows you the best practices of shell script programming. This book teaches effective shell script programming with Bash, and is ideal for people who may have used its command line but never really learned it in depth.